Investigation of the interactions between methadone and elvitegravir-cobicistat in subjects receiving chronic methadone maintenance. - Bruce, R Douglas; Winkle, P; Custodio, Jm; Wei, X; Rhee, M S; Kearney, Bp; Ramanathan, S; Friedland, Gerald H (Antimicrobial agents and chemotherapy, 2013)
Interactions between HIV and opioid dependence therapies are known to occur. We sought to determine if such interactions occurred between methadone and elvitegravir boosted with cobicistat (EVG/COBI). We performed a within-subject open-label pharmacokinetic and pharmacodynamic study of 11 HIV-seronegative subjects stabilized on at least 2 weeks of methadone. Subjects underwent baseline and steady-state evaluation of the effect of elvitegravir 150 mg once a day (QD) boosted with 150 mg QD of cobicistat (EVG/COBI) on methadone pharmacokinetic parameters. Safety and pharmacodynamics were monitored throughout the study. Compared to baseline values, the R-methadone mean area under the concentration-time curve to the end of the dosing period (AUCtau) (5,550 versus 6,210 h · ng/ml) and mean maximum concentration of drug in serum (Cmax) (316 versus 337 ng/ml) did not significantly increase in the presence of EVG/COBI. Compared to baseline values, the S-methadone mean AUCtau (7,040 versus 7,540 h · ng/ml) and mean Cmax (446 versus 452 ng/ml) did not significantly increase in the presence of EVG/COBI. The AUCtau, Cmax, and Ctau of elvitegravir and cobicistat did not significantly differ from those of historical controls. Opioid withdrawal or overdose was not observed among subjects in this study. The addition of EVG/COBI to stabilized patients receiving methadone did not affect methadone pharmacokinetics and pharmacodynamics. These two agents can be safely coadministered.
Keywords: Adult; Anti-HIV Agents; Area Under Curve; Carbamates; Drug Interactions; Female; Humans; Male; Methadone; Middle Aged; Narcotics; Opiate Substitution Treatment; Opioid-Related Disorders; Quinolones; Thiazoles